2014
DOI: 10.3390/ijerph110403586
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in Obese Type 2 Diabetes Patients is Associated with Increases in Insulin Resistance and IL-6 Cytokine Levels: Potential Targets for an Efficient Preventive Intervention

Abstract: Increased body weight as well as type 2 diabetes (T2D) are found to be associated with increased incidence of hypertension, although the mechanisms facilitating hypertension in T2D or nondiabetic individuals are not clear. Therefore, in this study we compared the levels of insulin resistance (IR:OGIS), plasma insulin (PI:RIA) levels, and pro-inflammatory cytokines (IL-6 and TNF-α: ELISA), being risk factors previously found to be associated with hypertension, in T2D patients showing increased body weight (obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 51 publications
1
63
2
4
Order By: Relevance
“…or only in obese individuals (38,45,46). We performed an analysis in order to investigate the influence of BMI in cytokine levels.…”
Section: Discussionmentioning
confidence: 99%
“…or only in obese individuals (38,45,46). We performed an analysis in order to investigate the influence of BMI in cytokine levels.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some studies suggest that the presence of a low-grade inflammation could predict the future onset of hypertension [9]. Lukic et al [9] showed that increases in inflammation might be an important factor influencing the occurrence of hypertension in obese patients with diabetes, but which was associated with the rise in interleukin-6 (IL-6).…”
Section: Resultsmentioning
confidence: 99%
“…Lukic et al [9] showed that increases in inflammation might be an important factor influencing the occurrence of hypertension in obese patients with diabetes, but which was associated with the rise in interleukin-6 (IL-6). Another pathogenic mechanism of hypertension onset may be attributed to the role of arterial stiffening which precedes the hypertension occurrence [20].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations